Les techniques de détection du VIH dans les échantillons humains - ACHIR, Safia; YOUNSI, Imane (My University, 2019)
This study on the différent direct and indirect techniques of HIV diagnoses in Alegria focused on a sample of 38 people whose blood was analyzed in two different medical institutions. At the level of the EPH the number of individuals was 33 (p1-p32 are blood donors, p33 is a hospitalized patient) and at the level of the IPA there were 5 patients infected with HIV. At the EPH level, ADALTIS rapid tests and combined ELISA tests were performed on 33 blood samples from 33 individuals. Among all the samples, only one showed a positive result but for which a confirmatory test was carried out at the IPA. At the level of the IPA, we carried out tests for detection of an HIV infection by rapid tests, WANTAI ELISA tests, ARCHITECT tests and WESTERN BLOT tests. For a last patient on anti-HIV treatment, real-time PCR was performed to assess the viral load. In this structure the results obtained are a patient with a positive diagnosis and three negative. For the patient whose viral load was to be measured, we observed an increase which shows that the recommended treatment is inappropriate..
Keywords: HIV diagnosis; ELISA; AIDS; Western blot; RT PCR; AIDS